Konsepsi Tentang Insan Kamil dalam Tasawuf - Simuh, Simuh (Al-Jami'ah: Journal of Islamic Studies, 1981)
Nama Tasawuf, Tasawuf dalam Bahasa inggris sering disebut Sufism. H.A.R Gibb misalnya mengatakan: There is room here only a brief summary of the beginings of the mystical movement in Islam which goes by the name of sufism. The origion of the term sufi is complex, but in general connected with the wearing of undyed garment of wool (suf). At first it was not a uniform but a mark of personal penitence, and some early ascetics comdemned the use of it. Ibn Sirin (d. 729) critized some early ascetics for wearing suf in imitation of jesus (as he said): I prefer to follow the example of the propehet who dressed in cotton. It appears that a particular group of ascetics but by the fourth century the wearing of wollen garments had becom the regular badge of the Sufis of Iraq and  the name was commonly applied to all mystics. Jadi kata tasawuf dan sufi dihubungkan dengan kebiasaan mereka mengenakan pakaiaan wool kasar atau pakaiaan yang umum bagi para fakir-miskin di Timur-Tengah pada masa itu. Mereka mengenakan pakaiaan wool kasar sebagai simbul atau sebagai tanda bahwa merekalah golongan yang lebih mengutamakan hidup sederhana, mementingkan kesucian Rohani, berlainan dari kebanyakan  umat Islam dimasa itu yang berlomba-lomba mengejar kesenangan hidup duniawi, berlomba dalam memakai pakaiaan yang indah-indah (sutra) dan mahal. Dengan demikiaan pemakaiaan wool kasar merupakan reaksi terhadap kecenderungan masyarakat yang mengejar kekayaan dan perhiasan duniawi, serta tidak memperhitungkan haram dean halal.